Papillote and Piopio: Drosophila ZP-domain proteins required for cell adhesion to the apical extracellular matrix and microtubule organization. - Bokel, C.; Prokop, A.; Brown, N.H. (Journal of Cell Science, 2005)
Adhesion between epithelial cells and extracellular substrates is normally mediated through basal adhesion complexes. However, some cells also possess comparable junctions on their apical surface. Here, we describe two new Drosophila proteins, Piopio and Papillote, that are required for the link between the apical epithelial surface and the overlying apical extracellular matrix (aECM). The two proteins share a zona pellucida (ZP) domain with mammalian aECM components, including the tectorins found in the vertebrate inner ear. Tagged versions of both proteins localized to the apical epithelial surface. Mutations in piopio, papillote and dumpy (another gene encoding a ZP-domain protein) cause defects in the innermost layer of the aECM and its detachment from the epidermis. Loss of Piopio, but not Papillote or Dumpy, causes the absence of specialized microtubule bundles from pupal wings, suggesting that Piopio plays a role in microtubule organization. Thus, ZP domain-containing proteins may have shared functions within the aECM, while also exhibiting specific interactions with the cytoskeleton.